1996
DOI: 10.1159/000139386
|View full text |Cite
|
Sign up to set email alerts
|

Trilinolein Preserves Mitochondria Ultrastructure in Isolated Rat Heart Subjected to Global Ischemia through Antioxidant Activity as Measured by Chemiluminescence

Abstract: Oxygen-derived free radicals (OFR) have been proposed as the cause of myocardial damage through lipid peroxidation during ischemia and reperfusion. Antioxidants can effectively ameliorate the damage induced by lipid peroxidation. Trilinolein is a triacylglycerol recently purified from the well known traditional Chinese herb Panax pseudoginseng, which has been used in treating circulatory disorders among Chinese for hundreds of years; it has linoleate as the only fatty acid residue in all three esterified posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…state disintegration of mitochonddal membrane and cdstae can be seen (Fig. lc), which was also observed in other studies (31,33). Our study showed lower yields of protein in the ischemic state as compared to control, which was also a finding of Jennings and Ganote (31).…”
Section: Discussionsupporting
confidence: 92%
“…state disintegration of mitochonddal membrane and cdstae can be seen (Fig. lc), which was also observed in other studies (31,33). Our study showed lower yields of protein in the ischemic state as compared to control, which was also a finding of Jennings and Ganote (31).…”
Section: Discussionsupporting
confidence: 92%
“…85-23. revised 1985]. This model has been described in detail elsewhere [11,13]. In brief, adult male Wistar rats (250-350 g) were heparinized (250 IU/kg) and anesthetized with 50 mg/kg pentobarbital intraperitoneally.…”
Section: Isolated Perfused Rat Heart Modeimentioning
confidence: 99%
“…a triacylglycerol recently puri fied from the traditional Chinese medicinal plant Panax pseudo-ginseng (Burk F.H. Chen), has been found to have potent antioxi dant activity and myocardial protective ef fects [10][11][12], Data concerning the changes in SOD activity during different periods ofhypoxia with or without subsequent normoxic perfusion are inconclusive. This study was undertaken to examine the changes in the activity of the two forms of SOD in an iso lated rat heart model during different modes of hypoxic or hvpoxic/normoxic perfusion and to determine whether the natural plant antioxidant, trilinolein, affects left ventricular performance and the changes in SOD during these procedures.…”
mentioning
confidence: 99%
“…Trilinolein exhibited concentration-dependent antioxidant activity at concentrations of between 0.1 nM and 1 ÌM, with a maximal free radical reduction of 48.0%, whereas trolox, a water-soluble analogue of vitamin E, showed a maximal mean reduction of 39.2% [4]. Similar to that of ·-tocopherol, trilinolein was previously reported to produce an antioxidant activity in a concentration-dependent manner [5]. In rat hearts pretreated with 0.1 ÌM trilinolein and subjected to 60 min of hypoxia, Cu,Zn-SOD activity was increased compared with baseline or with hearts subjected to 60 min of hypoxia without trilinolein [6].…”
Section: Discussionmentioning
confidence: 82%
“…Trilinolein has various beneficial effects, including the ability to reduce thrombogenicity, erythrocyte deformability, and arrhythmias, and it has been shown to possesses antioxidant activity in various experimental models [7]. The antioxidant effects of trilinolein produce a concentration-response curve similar to that of ·-tocopherol [5]. The myocardial protective effect of trilinolein is thought to be related to antioxidant activity through potentiation of superoxide dismutase (SOD) [6].…”
Section: Introductionmentioning
confidence: 99%